The Japanese economy - Ito, Takatoshi (The MIT Press, 2020)
The two authors provide a detailed and accessible economic history of Japan, delving into such topics as macroeconomics, growth, business cycles, and essential policy issues and, through an examination of financial regulation, monetary policy and fiscal policy, providing insights into Japan's banking crisis in the late 1990s and the global financial crisis of 2008-2009. Further explored are areas like savings, demography, and social security in the context of Japan's demographic transition, along with industrial organization, labor markets, international trade, international finance, and the Japan-US economic relationship.